Etmopterus marshae sp. nov, a new lanternshark (Squaliformes: Etmopteridae) from the Philippine Islands, with a revised key to the Etmopterus lucifer clade - Ebert, David A.; van Hees, Kelley E. (Zootaxa, 2018)
A new species of lanternshark, Etmopterus marshae (Squaliformes: Etmopteridae), is described from the Philippine Islands, western North Pacific Ocean. The new species occurs along insular slopes at a depth range of 322–337 m. The new species resembles other members of the “Etmopterus lucifer” clade in having linear rows of dermal denticles, and most closely resembles E. burgessi from Taiwan and E. evansi and E. pycnolepis from the South Pacific. It can be distinguished from all other members of the E. lucifer clade by a combination of characteristics, including length of anterior and posterior flank branches being of relatively equal length, straight vs. curved anterior flank marking, relative lengths of caudal markings, coloration, and relatively small size. A revised key to the revised key to the Etmopterus lucifer clade is provided.